2018
DOI: 10.1186/s12950-018-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental murine acute lung injury induces increase of pulmonary TIE2-expressing macrophages

Abstract: BackgroundBreakdown of the alveolo-capillary wall is pathognomonic for Acute Lung Injury (ALI). Angiopoietins, vascular-specific growth factors, are linked to endothelial barrier dysfunction, and elevated Angiopoietin-2 (ANG2) levels are associated with poor outcome of ALI patients. Specialized immune cells, referred to as ‘TIE2-expressing monocytes and macrophages’ (TEM), were shown to specifically respond to ANG2 binding. However, their involvement in acute inflammatory processes is so far completely undescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…In animal models of sepsis, loss of Tie2 — both cell surface receptor and Tie2 phosphorylation — is a common feature of several infectious diseases associated with vascular leak ( 41 ). Tie2 is also expressed on a subpopulation of monocytes and recruitment and/or these cells via Angpt-2 may promote pathologic lung injury through secretion of matrix-degrading enzymes and/or inflammatory cytokines ( 44 , 45 ). The role of Tie2 on nonendothelial cells is incompletely defined, and it is difficult to speculate on their role in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of sepsis, loss of Tie2 — both cell surface receptor and Tie2 phosphorylation — is a common feature of several infectious diseases associated with vascular leak ( 41 ). Tie2 is also expressed on a subpopulation of monocytes and recruitment and/or these cells via Angpt-2 may promote pathologic lung injury through secretion of matrix-degrading enzymes and/or inflammatory cytokines ( 44 , 45 ). The role of Tie2 on nonendothelial cells is incompletely defined, and it is difficult to speculate on their role in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their proangiogenic potential, TEMs also possess distinct immunomodulatory characteristics; for instance, acute inflammation was shown to promote Tie2 expression in macrophages and upregulate the activity of TEMs. 35 TEMs were also shown to suppress T-cell activation and promote regulatory T-cell expansion in human cancer. 36 In a recent study, Ang2/Tie2+ circulating monocytic myeloid-derived suppressor cell axis was found to participate in tumor immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is still unclear whether the predominately M1 MF population we observed contributes to the killing of O. tsutsugamushi and the damage of vascular tissues, as seen for protective versus pathogenic roles in other lung infection models [60]. Since a significant Ang2 release and Tie2 decrease was detected at D6, followed by strong polarization to M1 MFs (Figs 2-4), it will be important to examine whether endothelial activation precedes the MF polarization and contributes to the strong M1 phenotype via the release of endothelial factors, such as Ang2, particularly on Tie2 expressing monocytes/ MFs [61]. Given the reports that anti-Ang2 antibody treatment during pulmonary bacterial infection can decrease MF recruitment and inflammation [29], and that signaling via Tie2 on monocytes/MFs can promote a proinflammatory profile [62], it will be interesting to determine how Ang2/Ang1 signaling on both endothelial cells and MFs promote cellular recruitment and activation during O. tsutsugamushi infection.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%